PERKEMBANGAN MASA DEWASA MENENGAH (USIA 41 - 60 TAHUN) KONTEKS AL QURAN DAN HADITS - Jufri, Muhammad Haeril; Mutmainnah, Besse; Santalia, Indo; Pujirana, Andi Isni (UIN Sumatera Utara Medan, 2025)
Middle adulthood (ages 41-60) is a critical transitional stage in human life marked by physical, psychosocial, and cognitive changes. This article provides a comprehensive overview of biological transformations such as muscle mass decline, hormonal shifts, and gradual organ function deterioration, all of which significantly impact quality of life. It also addresses psychosocial challenges including identity crises, the pressures of being part of the “sandwich generation,” marital conflicts, and mental health issues. Cognitively, this stage offers potential for growth in critical, logical, and integrative thinking, supported by accumulated life experience. A multidisciplinary approach, including Islamic perspectives, is employed to offer a holistic understanding of this life phase. The article further outlines adaptive strategies to support individuals during middle adulthood, such as regular physical activity, cognitive training, social engagement, and spiritual development. With appropriate understanding and support, middle adulthood can become a meaningful and productive period of life.